2017
DOI: 10.1074/jbc.a116.731190
|View full text |Cite
|
Sign up to set email alerts
|

Substrate recognition by the Cdh1 destruction box receptor is a general requirement for APC/CCdh1-mediated proteolysis.

Abstract: There were several errors in this article. In the Cdc5 experiment in Fig. 3A, the anti-G6PD immunoblot image from the Spo13 experiment in Fig. 3B was accidentally duplicated and flipped horizontally. Also in Fig. 3A, the experiment labeled Nrm1 actually shows the results from the Mps1 experiment. In Fig. 4C, the Spo12 stability profile in the wild-type CDH1 strain is identical to that shown in Fig. 3B. In Fig. 4, B and C, a black bar is now used to indicate excision of lanes from the same exposure of the same… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…At anaphase onset, the anaphase‐promoting complex/cyclosome (APC/C) is activated to catalyze securin degradation and trigger chromosome segregation. At the same time, mitotic cyclins start to be degraded, followed by Polo and Aurora kinases (Shirayama et al , ; Lindon & Pines, ; Qin et al , ). Condensed mitotic chromosomes must first be fully separated on an elongating anaphase spindle, before the spindle subsequently disassembles and chromosomes decondense.…”
Section: Introductionmentioning
confidence: 99%
“…At anaphase onset, the anaphase‐promoting complex/cyclosome (APC/C) is activated to catalyze securin degradation and trigger chromosome segregation. At the same time, mitotic cyclins start to be degraded, followed by Polo and Aurora kinases (Shirayama et al , ; Lindon & Pines, ; Qin et al , ). Condensed mitotic chromosomes must first be fully separated on an elongating anaphase spindle, before the spindle subsequently disassembles and chromosomes decondense.…”
Section: Introductionmentioning
confidence: 99%
“…In the past 15 years, high-resolution X-ray and cryo-EM (electron microscopy) studies of the APC/C and its interactions with substrates and E2s has generated a detailed description of the structure-function relationships that drive ubiquitination and degradation (Barford 2020). The binding of Cdc20 or FZR1 to the core APC/C creates at least three degron-binding sites for the known APC/C degrons, namely the "Destruction-box" (D-box, consensus RxxLxxxxN) and KEN motifs, and the ABBA motif thought to be required for Cyclin A degradation only (Qin et al 2017). A cryo-EM study of the structure of APC/C-FZR1 in complex with its pseudo-substrate inhibitor Acm1 revealed simultaneous engagement of D-box, KEN, and ABBA motifs of Acm1 with their respective receptor sites on the interactions (He et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The determination of the molecular structure of the APC/C complex indicated that coactivators are involved in the KEN-box recognition (Chao et al, 2012), while they partner with the Apc10 subunit to interact with the D-box motif (Da Fonseca et al, 2011). Strikingly the conformation changes occurring in the APC/C complex upon recognition of the D-boxes is a requirement to process all of the substrates, although many of them lack canonical D-boxes (Qin et al, 2017). Although it is not general, in some cases, APC/C substrates are regulated by phosphorylation of recognition motifs, resulting in the absence of APC/C recognition.…”
Section: Apc/c Cdh1/fzr-1 Regulationmentioning
confidence: 99%